HUBUNGAN BEBAN KERJA DENGAN KINERJA PERAWAT DI INSTALASI RAWAT INAP RUMAH SAKIT HARAPAN BUNDA KOTA BATAM - TrisyaYona Febrina; Zulkarnain Edward; Nurhafizah Nasution (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
The workload is the frequency of activity - average of each - each job within a certain period. Performance(performance) is a result of work achieved in executing tasks - tasks assigned to them based on skills,experience and seriousness as well as time. The performance of nurses is a problem as long as they are notyet aware of the workload that includes the number of patients, the level of dependence of the patient, thetype of activities to be carried out, the average time of nursing actions, assignment system and facilitieswhich he is responsible for properly implemented. The purpose of this study was to see RelationshipBetween Workloads with performance Inpatient Nurse in HarapanBunda Hospital Batam. This type ofresearch is analytic by using